2018
DOI: 10.21467/ias.4.1.14-19
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of an Anionic Dye, Eosin Yellow onto Pineapple Peels: Isotherm and Thermodynamic Study

Abstract: A B S T R A C TEosin Yellow (EY), an anionic dye (acid dye) was adsorbed using an agricultural waste, pineapple peels (PP) as bio-sorbent in order to investigate its suitability as an alternative adsorbent, and to give insight into the mechanisms of binding. The study includes: equilibrium isotherms and thermodynamics studies. The adsorption isotherm and thermodynamics experiments were conducted using batch equilibrium techniques. The adsorption data were fitted into Langmuir, Freundlich and Temkin isotherm mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…DFT studies revealed that adsorption of EY on 1 is primarily due to π-π interactions. [53] γ-Al 2 O 3 Nanoparticles 47.78 [54] Teak leaf litter powder 31.64 [55] Silica functionalized with 1-propyl-3-methylimidazolium chloride 17.73 [56] Pineapple peels 11.76 [57] Clay/Carbon Composite' 11.15 [51] Journal of Inorganic and General Chemistry Zeitschrift für anorganische und allgemeine Chemie…”
Section: Discussionmentioning
confidence: 99%
“…DFT studies revealed that adsorption of EY on 1 is primarily due to π-π interactions. [53] γ-Al 2 O 3 Nanoparticles 47.78 [54] Teak leaf litter powder 31.64 [55] Silica functionalized with 1-propyl-3-methylimidazolium chloride 17.73 [56] Pineapple peels 11.76 [57] Clay/Carbon Composite' 11.15 [51] Journal of Inorganic and General Chemistry Zeitschrift für anorganische und allgemeine Chemie…”
Section: Discussionmentioning
confidence: 99%
“…Improper disposal practices of materials containing eosin yellowish dye particles can also cause environmental contamination, whether through direct dumping or incineration, releasing harmful substances into air, soil, or water. To mitigate these impacts, it is essential for industries to implement proper wastewater treatment procedures, adopt sustainable practices, and explore greener alternatives with lower toxicity and reduced environmental persistence (Ahmed et al, 2011: Fabian et al, 2022. Furthermore, regulatory measures and responsible handling and disposal practices are crucial in minimizing the environmental footprint of eosin yellowish and ensuring its safe use in a manner that preserves environmental integrity.…”
Section: Introductionmentioning
confidence: 99%
“…It has various applications in different fields; because of its vivid color, it is practically used in printing ink, dyeing, leather industry, printing, etc. (Gouvêa et al, 2000). In addition, Eosin Yellowish is effective for depolarization in biological methods because of its complex aromatic structure and stability (Daneshvar et al, 2003).…”
Section: Introductionmentioning
confidence: 99%